Simplify `root(3)(128a^(13)b^(6))` :

A radical expression is simplified if there are no fractions in the radicand, no radicals in the denominator, and no perfect nth power factors in the radicand.

In this case, we need to get rid of any perfect cubes in the radicand.

Rewrite as `root(3)(64a^(12)b^(6)2a)` Then use `root(n)(ab)=root(n)(a)root(n)(b)` to get:

`root(3)(64a^(12)b^6)root(3)(2a)`

**`=4a^4b^2root(3)(2a)` which is the simplified form.**

** `root(3)(64)=4` since `4^3=64` . Also `root(3)(a^(12))=a^4` since `(a^4)^3=a^12` .

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.